Morpho-anatomy of native species used as substitute of quina (Cinchona spp.) in Brazilian traditional medicine : Esenbeckia febrifuga - Somavilla, Nádia Sílvia (2018)
Esenbeckia febrifuga (A.St.-Hil.) A. Juss. ex Mart., Rutaceae, is known by several popular names including quina-do-mato. This name is a reference to the use of its bark as febrifuge and in the past was employed as a substitute of Cinchona sp. for treatment of malaria symptoms. This confusion may have been reinforced by the fact that the bark of these plants are similar in appearance and have a bitter taste. In view thereof this study presents the description morphological and anatomical and the histochemistry of the stem bark and contributes to the pharmacobotanical study of plant drugs identified as Brazilian quinas, in sequence to two others studies. Compared with the Cinchona species, the prismatic shape of calcium oxalate crystals and the fibers with adornate end walls proved to be the main characteristics for differentiation.